Perancangan Interior Gelanggang Olahraga Grogol Jakarta dengan Gaya Kontemporer - Elizabeth Gloria Mariani Kaunang; Sakundria Satya Murti Wardhana (MAN 4 Kota Pekanbaru, 2026)
The design of sports arena interiors currently emphasizes not only functional aspects but also user comfort, aesthetics, and spatial identity that reflect contemporary needs. This study aims to design the interior of Grogol Sports Arena, Jakarta, using a contemporary design approach to improve spatial quality, user comfort, and functionality. The research employed a descriptive qualitative method through field observations, interviews with users and managers, documentation, literature studies, and comparative studies with other sports facilities. The design process adopted Rosemary Kilmer’s design method, which includes problem identification, data collection, concept development, design refinement, and evaluation stages. The results indicate that the application of contemporary concepts through efficient zoning, functional circulation, modern materials, dynamic color schemes, optimal lighting, and integrated safety systems can create a more comfortable and attractive sports environment. The proposed design is expected to enhance user experience while supporting sports and social activities in urban public spaces.